TRACING THE CONCEPT OF FAJR IN THE ISLAM MOSAIC AND MODERN SCIENCE - Susiknan Azhari (Universitas Islam Negeri Jakarta, 2018)
This article is an attempt at tracing several points of view concerning the precise time of Fajr. The study suggests that different concepts of fajr in the world of Islam arose for two reasons: the Imamah Jibril hadith is too general in notion and the different ways in understanding the “ghalas” and “isfar” hadith without considering the conditioin and weather by the time the hadith was spoken. In addition, moslem astronomers focus on the empirical observation on the position of the sun and neglects the nas of the message. This, in turn, urges the truth claim.